2003
DOI: 10.1038/sj.ejcn.1601564
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in a cohort of black Jamaican children as estimated by BMI and other indices of adiposity

Abstract: Objective: To examine the relationships of body mass index (BMI) to obesity indices derived from anthropometry and to determine tracking of overweight between late childhood and early adolescence, in a cohort of children with mixed nutritional history. We also compared identification of overweight children using The International Obesity Task Force (IOTF) BMI cut-off points with skinfolds. Design: Prospective study. Setting: Kingston, Jamaica. Subjects: A total of 306 children examined at 7 -8 y and at 11 -12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
37
1
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 30 publications
(31 reference statements)
14
37
1
7
Order By: Relevance
“…In relation to specificity, Gaskin et al 16 showed similar results in Jamaican youth when comparing over-weight prevalence according to the IOTF classification 5 with that found by subscapular skinfold. However, the study showed low sensitivity, classifying 25% of obese adolescents as normal (false negatives).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In relation to specificity, Gaskin et al 16 showed similar results in Jamaican youth when comparing over-weight prevalence according to the IOTF classification 5 with that found by subscapular skinfold. However, the study showed low sensitivity, classifying 25% of obese adolescents as normal (false negatives).…”
Section: Discussionsupporting
confidence: 51%
“…However, as in the current study, they found high specificity with the IOTF method 5 , independently of the sexual maturation period. The differences observed between the studies may result from the criterion used as the gold standard, since our study used the 85 th percentile and skinfolds, while Chiara et al 14 and Gaskin et al 16 used only the subscapular skinfold. The choice of method to estimate the percentage of body fat is a potential source of variation in sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 60%
“…BMI and WHR and constitutes an increased risk for several adult degenerative diseases (18). Inadequate nutrition in early childhood (more common among socially disadvantaged populations) may serve to potentiate adult obesity-related disease (19).…”
Section: Discussionmentioning
confidence: 99%
“…Selection of appropriate tools is complicated by the fact that most tools in use are proxy measures that do not actually measure adiposity 15 and vary in validity 16 depending on the age and ethnicity of the population 17 . Body mass index (BMI) is one such measure 1,2 where, in addition to the difficulty of selecting appropriate equations for calculating body composition from BMI, there is the added effect of differences in the rate of maturation and its effect on body composition 15 .…”
mentioning
confidence: 99%